Procedural influences on compression and injection moulded cellulose fibre-reinforced polylactide (PLA) composites: Influence of fibre loading, fibre length, fibre orientation and voids. (February 2016) - Graupner, Nina; Ziegmann, Gerhard; Wilde, Fabian; Beckmann, Felix; Müssig, Jörg
Abstract: The influence of fibre loading (20, 30, 40 mass%), fibre fineness, and the processing procedure (compression moulding – CM and injection moulding – IM) on the tensile and impact strength of lyocell/PLA composites was examined. The results revealed a significantly higher tensile and impact strength for CM composites compared to IM composites. An increase in strength up to a fibre loading of 40% was determined for CM composites, while for IM composites the highest values were measured at a fibre loading of 30%. Composites were investigated for their void content, fibre orientation, fibre length and process-induced fibre damage. A better fibre/matrix adhesion and compaction of IM composites was found while fibre orientation as well as mechanical properties of extracted fibres show no significant differences between CM and IM composites. The different mechanical characteristics of CM and IM samples are attributed predominantly to the fibre aspect ratio and the distribution of voids.